Improving pediatric endocrinology trainees' knowledge about insulin pumps and continuous glucose monitors with online spaced education: Technology Knowledge Optimization in T1D (TeKnO T1D). Issue 5 (6th April 2020) - Marks, Brynn E.; Waldman, Gretchen; Reardon, Kathleen; Terrio, Shannon; Kumar, Anshul; Stafford, Diane E. J.; Garvey, Katharine C.; Wolfsdorf, Joseph I.
Abstract: Objective: We explored the impact of TeKnO T1D, an online, case‐based, spaced education curriculum about insulin pump and continuous glucose monitor (CGM) use in pediatric type 1 diabetes management. Methods: Pediatric endocrinology fellows (n = 64) were randomized to receive an educational curriculum focused on either insulin pumps or CGMs. Fellows received interactive questions twice weekly via email or mobile app. Median time to completion was 76.5 days. The primary outcome was change in knowledge as measured by performance on multiple‐choice questions (MCQ) from the pre‐test to the post‐test. Results: Forty‐eight of 64 (75%) learners completed the curriculum and assessments. The pump group improved from 35.0 ± 15% on the pre‐test MCQs to 61.1 ± 17% on the post‐test, a 12.2 absolute percentage point greater improvement on pump‐specific items than the CGM group ( P = .03). The CGM group improved from 30.3 ± 15% on the pre‐test MCQs to 61.4 ± 21% on the post‐test, a 28.7 absolute percentage point greater improvement on CGM‐specific items than the pump group ( P  < .001). Both groups were more likely to report an appropriate level of understanding of their respective technologies after completing the corresponding curriculum. In thematic analysis of qualitative data, fellows indicated that knowledge gains led to improved patient care. There was universal agreement about enjoyment and effectiveness of the curricula. Conclusions: TeKnO T1D proved to be an engaging, effective way to improve endocrinology fellows' knowledge and confidence about insulin pumps and CGM use in the management of pediatric type 1 diabetes.